2010
DOI: 10.1007/s00380-010-0060-x
|View full text |Cite
|
Sign up to set email alerts
|

Olmesartan reduces arterial stiffness and serum adipocyte fatty acid-binding protein in hypertensive patients

Abstract: Adipocyte fatty acid binding protein (A-FABP) has been reported to be involved in insulin resistance, lipid metabolism, and atherosclerosis; however, little is known about the effect of medication on the change in circulating A-FABP in human subjects. We evaluated the effects of angiotensin II type 1 receptor blocker (ARB) on arterial stiffness and its association with serum A-FABP in patients with hypertension. Thirty patients newly diagnosed with essential hypertension were treated with olmesartan (20 mg/day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 32 publications
2
36
0
2
Order By: Relevance
“…First, the number of subjects enrolled in study 1 was small, and the possibility of type 1 error in statistical tests cannot be excluded. Second, most of the study subjects had been treated with several drugs at baseline, including angiotensin II receptor blockers ( 33,49 ) and a statin ( 50 ), which have been reported to affect circulating FABP4 concentration. Therefore, such drugs might have modulated the change in FABP4 level.…”
Section: Studymentioning
confidence: 99%
“…First, the number of subjects enrolled in study 1 was small, and the possibility of type 1 error in statistical tests cannot be excluded. Second, most of the study subjects had been treated with several drugs at baseline, including angiotensin II receptor blockers ( 33,49 ) and a statin ( 50 ), which have been reported to affect circulating FABP4 concentration. Therefore, such drugs might have modulated the change in FABP4 level.…”
Section: Studymentioning
confidence: 99%
“…Therefore, early intervention with angiotensin II receptor blockers and statins seems to have beneficial effects on abnormalities in structure and function of the LA, LV, and aorta in this type of patient. [30][31][32][33] …”
Section: Disclosuresmentioning
confidence: 99%
“…In a small study of 10 patients with mild-to-moderate hypertension, olmesartan medoxomil did not reduce BP significantly, but did produce significant reductions in hsCRP and appeared to improve myocardial function independent of BP lowering [19]. In another study, hsCRP levels significantly dropped in hypertensive patients who were treated with olmesartan for 6 month [102]. In nondiabetic patients with hypertension and the metabolic syndrome, both olmesartan medoxomil plus amlodipine and olmesartan medoxomil plus HCTZ effectively reduced BP and CRP with no differences between groups.…”
Section: Hscrpmentioning
confidence: 94%
“…However, arterial index decreased significantly with monotheraphy and combination therapy in this study. On the other hand, another recent study showed that monotheraphy with olmesartan does significantly decrease arterial stiffness [102].…”
Section: Capmentioning
confidence: 99%